Flood disaster mitigation on road sections: Optimizing performance by implementing traffic engineering management - Puspa Jayanti Erviela; Sarjana Sri; Karyanto Yudi; Oktosatrio Suhendro; Gogo Mulia Farel (E3S Web of Conferences)
Flood disaster mitigation efforts are carried out through traffic engineering management to reduce the negative impacts of flooding on the community and infrastructure, where these efforts require a comprehensive disaster management plan and involve cooperation between the government, traffic authorities, emergency services and the surrounding community. This study aims to determine the traffic engineering scenario that can reduce congestion and improve traffic performance during floods. This study analyzes the road network in Gedebage District and Ujung Berung City which are affected by floods under normal conditions, flood conditions (do-nothing), and conditions when the traffic engineering scenario is applied (do-something) by developing an origin-destination matrix formed using the Furness method, traffic modelling using PTV Visum and traffic performance analyzed using the 2023 Indonesian Road Capacity Guidelines method. The results of the study indicate that there is an increase in traffic performance during floods with the implementation of do-something scenario 2. The study recommends that stakeholders implement flood disaster mitigation by providing information on mapping flood-prone areas, early warning systems, information on evacuation routes and emergency routes, and alternative routes.